Demographic Processes – History, Trends, Prospects - Cholakov, Nikola (Research Papers, 2012)
In this study demographic processes are reviewed together with the concept of the demographic transition and other population theories as well as some of the recognized expectations of the future of the population. There are plenty of peculiarities in the demographic situation in developed countries, including Bulgaria, among which is the decline of birth process during the second half of the 20th century and the social and economic consequences of it. The decline of birth process is a result of numerous interconnected factors which are difficult to trace let alone to explain. Hence different and often contradictious explanations of this phenomenon. During the last decades the science more often turns to the future of the demographic processes and different population projections are elaborated which reveal what to expect and what not to expect from the future in this area.